2011
DOI: 10.5216/pat.v41i4.12388
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento De Fungos Em Sementes De Trigo

Abstract: está concentrada no Sul do Brasil. O cereal vem sendo introduzido paulatinamente na região do Cerrado, sob irrigação ou sequeiro (Embrapa 2007). Desde dezembro de 2003, o Estado de Mato Grosso está oficialmente incluso no zoneamento agrícola do Ministério da Agricultura, Pecuária e Abastecimento (MAPA), por meio da Portaria 131, a qual estabelece o plantio de trigo sequeiro entre 1º e 29 de fevereiro, em regiões com altitude igual ou superior a 750 m, e o plantio irrigado entre 21 de abril e 20 de maio, em mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Similar to the results found by Barreto et al (2015) that also verified a low incidence (4.6%) of this fungus in cowpea (V. unguiculata). Kobayasti et al (2011) found that the seed deterioration the smooth top (Jatropha curcas L.) is related to the presence of Chaetomium sp. The action of this pathogen depends on the physical and physiological conditions of the seeds and the environmental factors that predominate during the storage (Ruiz Filho et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the results found by Barreto et al (2015) that also verified a low incidence (4.6%) of this fungus in cowpea (V. unguiculata). Kobayasti et al (2011) found that the seed deterioration the smooth top (Jatropha curcas L.) is related to the presence of Chaetomium sp. The action of this pathogen depends on the physical and physiological conditions of the seeds and the environmental factors that predominate during the storage (Ruiz Filho et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The fungus infects mainly spikes and is common its occurrence in combination with Fusarium species. In addition to infection on spikes, leaf lesions may also occur under hot and humid conditions (Kohli et al, 2011;Saharan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Through seeds, microorganisms can be transported for long distances and easily introduced into new areas (Nasser, 1987). The incidence of F. graminearum on seeds was quantified in many studies (Telles Neto et al, 2007;Kabeere et al, 1997;Garcia Júnior et al, 2008;Kobayasti and Pires, 2011) and could be up to 48% (Kabeere et al, 1997;Danelli et al, 2012). For P. grisea, the pathogen incidence was also measured in different studies, and most of them reported incidences about 6 to 18% (Goulart and Paiva, 1991;Goulart and Paiva, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…200 seeds were used, divided into four repetitions and placed in gerbox, seed dispersal on two sheets of paper germiteste sterile and moistened with distilled and autoclaved water in proportion to 2.5 times your weight [22]. A solution of 1.05% sodium hypochlorite was …”
Section: Sanitary Evaluationmentioning
confidence: 99%